Loading [MathJax]/jax/output/SVG/jax.js
 

Mathefreaker2021

avatar
BenutzernameMathefreaker2021
Punkte941
Membership
Stats
Fragen 73
Antworten 262

 #1
avatar+941 
0

For part (a), we can use the AM-GM (Arithmetic Mean-Geometric Mean) inequality, which states that for any positive real numbers a_1, a_2, ..., a_n, their arithmetic mean is always greater than or equal to their geometric mean:

(a1+a2+...+an)/n>=sqrt[(a1a2...an)(1/n)]

Using this inequality repeatedly, we can prove the given inequality as follows:

(a2+b2)2(c4+d4)(e4+f4)=[(a2+b2)2][(c4+d4)(e4+f4)]

By AM-GM,

[(a2+b2)2][(c4+d4)(e4+f4)]>=[(a2+b2)2][sqrt[(c4d4e4f4)(1/4)]]

And by AM-GM again,

[(a2+b2)2][sqrt[(c4d4e4f4)(1/4)]]>=[(a2+b2)2][sqrt[(c2d2e2f2)(1/2)]]

Finally, by AM-GM once more,

[(a2+b2)2][sqrt[(c2d2e2f2)(1/2)]]>=[(a2+b2)(1/2)][(cdef)(1/2)]2

Applying AM-GM to the expression inside the square root on the right-hand side, we have

[(a2+b2)(1/2)][(cdef)(1/2)]2>=[(a2+b2)(1/2)][2(abcdef)(1/6)]2

Finally, squaring both sides, we get

[(a2+b2)2][(cdef)(1/2)]2>=32abcdef, as desired.

For part (b), we can use the AM-GM inequality directly:

(a2+b2)(c2+d2)(e2+f2)=(a2+b2)[(c2+d2)(e2+f2)]

By AM-GM,

(a2+b2)[(c2+d2)(e2+f2)]>=(a2+b2)2sqrt[(c2d2)(e2f2)]

By AM-GM again,

(a2+b2)2sqrt[(c2d2)(e2f2)]>=2(a2

.
 #1
avatar+941 
0

(a) The left-hand side counts the number of ways to choose k elements from a set of n - 1 elements. The first term, C(n - 1, k - 1), counts the number of ways to choose k - 1 elements, and the second term, C(n - 1, k), counts the number of ways to choose k elements. To form the set of k elements in C(n, k), we simply add an element n to each of these two sets. So, C(n - 1, k - 1) + C(n - 1, k) = C(n, k).

(b) The left-hand side counts the number of ways to choose 0 to n elements from a set of n elements. For each positive integer i from 0 to n, C(n, i) counts the number of ways to choose i elements. The sum on the left-hand side is equivalent to counting the number of possible combinations of n elements, which is 2^n.

(c) The left-hand side counts the number of ways to choose 0 to k elements from a set of n + k elements. Each term C(n + i, i) counts the number of ways to choose i elements from a set of n + i elements. The sum on the left-hand side is equivalent to counting the number of possible combinations of n + k elements, which is C(n + k + 1, k).

(d) The left-hand side counts the number of ordered pairs (X, Y) where X is a set of r elements selected from a set of m elements and Y is a set of r elements selected from a set of n elements. For each positive integer i from 0 to r, C(m, i) C(n, r - i) counts the number of ordered pairs where X has i elements and Y has r - i elements. The sum on the left-hand side is equivalent to counting the number of possible combinations of r elements from the set of m + n elements, which is C(m + n, r).

(e) The left-hand side counts the number of ordered pairs (a, b) of positive integers where 1 <= a, b <= n. The expression (n + 1)^2 - 2n - 1 counts the total number of ordered pairs of positive integers where 1 <= a, b <= n + 1 and then subtracts the ordered pairs (n + 1, n + 1) and (n + 1, i) for 1 <= i <= n, as well as (i, n + 1) for 1 <= i <= n. This gives us the total number of ordered pairs of positive integers where 1 <= a, b <= n.

(f) The left-hand side counts the number of ordered triples (a, b, c) of positive integers where 1 <= a, b, c <= n. The expression (n + 1)^3 - 3n^2 - 3n - 1 counts the total number of ordered triples of positive integers where 1 <= a, b, c <= n + 1 and then subtracts the ordered triples (n + 1, n + 1, n + 1), (n + 1, n + 1, i), (n + 1, i, n + 1), and (i, n + 1, n + 1) for 1 <= i <= n, as well as all ordered triples where at least one element is equal to n + 1. This gives us the total number of ordered triples of positive integers where 1 <= a, b, c <= n.

 #1
avatar+941 
0

This inequality can be proven using the Cauchy-Schwarz inequality.

Let x=sqrt(a2+ab+b2),y=sqrt(a2+ac+c2), and z=sqrt(b2+bc+c2), then we can rewrite the inequality as:

x+y+z>=sqrt(3)(sqrt(ab)+sqrt(ac)+sqrt(bc))

Squaring both sides, we get:

(x+y+z)2>=3(sqrt(ab)+sqrt(ac)+sqrt(bc))2

Expanding the left-hand side, we get:

x2+y2+z2+2xy+2xz+2yz>=3(sqrt(ab)+sqrt(ac)+sqrt(bc))2

Expanding the right-hand side, we get:

x2+y2+z2+2xy+2xz+2yz>=3(ab+ac+bc+2sqrt(ab)sqrt(ac)+2sqrt(ab)sqrt(bc)+2sqrt(ac)sqrt(bc))

Using the Cauchy-Schwarz inequality, we have:

2xy+2xz+2yz>=2(sqrt(ab)sqrt(ac)+sqrt(ab)sqrt(bc)+sqrt(ac)sqrt(bc))

Substituting this into the previous inequality, we get:

x2+y2+z2+2xy+2xz+2yz>=3(ab+ac+bc)+2(sqrt(ab)sqrt(ac)+sqrt(ab)sqrt(bc)+sqrt(ac)sqrt(bc))

Using the definition of x, y, and z, we get:

(a2+ab+b2)+(a2+ac+c2)+(b2+bc+c2)+2sqrt((a2+ab+b2)(a2+ac+c2))+2sqrt((a2+ab+b2)(b2+bc+c2))+2sqrt((a2+ac+c2)(b2+bc+c2))>=3(ab+ac+bc)+2(sqrt(ab)sqrt(ac)+sqrt(ab)sqrt(bc)+sqrt(ac)sqrt(bc))

Combining like terms and rearranging, we get:

2(sqrt((a2+ab+b2)(a2+ac+c2))+sqrt((a2+ab+b2)(b2+bc+c2))+sqrt((a2+ac+c2)(b2+bc+c2)))>=2(sqrt(ab)sqrt(ac)+sqrt(ab)sqrt(bc)+sqrt(ac)sqrt(bc))

So, the inequality is proven.

Equality occurs when x = y = z, which meansa2+ab+b2=a2+ac+c2=

.